CERAMIC MATERIAL OF «TITANIUM OXIDE – ALUMINIUM OXIDE – SOLID LUBRICANT» SYSTEM - V. A. Okovity; O. G. Devoino; А. F. Panteleenko; V. V. Okovity (Наука и техника)
The paper presents an oxide ceramic material with addition of solid lubricant which has good technological characteristics and which is able to form high wear-resistant plasma coatings with low friction coefficient.